Institutional systems inducing R&D in Amazon- the role of an investor surplus toward stakeholder capitalization. (November 2020) - Watanabe, Chihiro; Tou, Yuji; Neittaanmäki, Pekka
Abstract: Amazon demonstrated a conspicuous increase in R&D and became the world's top R&D firm in 2017 with a skyrocketing increase in market capitalization, making it close to being the world's biggest company. Such a remarkable accomplishment can be attributed to Amazon's institutional systems, which orchestrate techno-financing systems that fuse a unique R&D transformation system and a sophisticated financing system centered on the cash conversion cycle (CCC). These institutional systems support and endorse aggressive investment in R&D that incorporates the characteristics of uncertainty, a long lead time, and successive inflows of very large amounts of funding without interruption. While some of this investment can be endorsed by Amazon's positive business results in terms of a sustained increase in sales and free cash flow, such a large amount of aggressive investment is beyond endorsement. In addition to actual economic performance, investors have been betting on a high level of risky investment with the expectation of Amazon's future success by trusting its R&D-inducing institutional systems. While the former can be considered to be a general reaction to a producer surplus, the latter can be postulated as an investor surplus in which investors bet on overly optimistic future prospects instead of actual accomplishments. This is similar to a consumer surplus in which consumers pay more than the actual market price for attractive goods and services. By introducing a concept of gross market value consisting of a producer surplus and an investor surplus, this paper attempts to elucidate the institutional systems that enable Amazon to invest a very large amount of financing resources in aggressive R&D. An intensive empirical analysis focusing on the development trajectory of Amazon's techno-financing system over the last two decades was conducted, together with comparative analyses of the performance of the big four online service companies, Google, Apple, Facebook, and Amazon (GAFA). It was identified that among GAFA, Amazon demonstrated the highest dependence on an investor surplus, which suggests that investors are betting on the continuation of Amazon's solid growth by means of its aggressive investment in R&D, supported and endorsed by its institutional systems. This idea is supported by the high elasticity of its investor surplus to R&D investment. Noteworthy is that investors incorporate not only shareholders but also broad stakeholders centered on users, and that they expect not only economic value but also supra-functionality beyond such value. A broadly applicable practical approach for measuring an investor surplus and an insightful suggestion highlighting the significance of an investor surplus toward stakeholder capitalism are thus provided. Highlights: Institutional systems inducing Amazon's conspicuous R&D investment was elucidated. A concept of gross market value which reflects the value of the institutional systems was introduced. A broadly applicable practical approach for measuring an investor surplus was provided. Amazon's high dependence on an investor surplus was demonstrated. The significant role of an investor surplus toward stakeholder capitalization was postulated.